Leveraging Human Capital for Remote Work: A Case Study of the Cooler and Freezer Repair Industry in Malaysia - Riwayadi, Eko; Umran, Fankar M; Monoarfa, Maya; Saleh, Hendra Noor; Tahjoo, Anastasia (Indonesian Journal of Business Analytics, 2024)
This case study analysis examines the impact of human capital on the performance, productivity, and competitive advantage of an organization operating in the cooler and freezer repair and maintenance industry. The analysis reveals key findings related to field service operations, customer satisfaction, service quality, and workforce management. The study identifies challenges and opportunities, including skill gaps and training needs, workforce capacity and availability, retention and talent management, and effective communication and collaboration. Based on these findings, actionable recommendations provided to address the identified challenges and leverage opportunities. The recommendations emphasize the importance of continuous training, knowledge transfer, recruitment strategies, employee retention initiatives, improved communication channels, and enhanced collaboration. These recommendations aim to optimize the organization's field service operations, improve service quality, and enhance customer satisfaction. The case study highlights the critical role of human capital in organizational success.